(untitled) (Community Based Medical Journal, 2013)
The case is presented to discuss clinical signs, diagnostic tools and therapeutics of anterior urethral valves, an obstructive anomaly of the urinary system in males. Signs of urinary tract obstruction were identified on pre-natal ultrasound in a male fetus and the diagnosis of anterior urethral valves was made through post-natal evaluation. As an initial treatment, vesicostomy was performed in the patient. Later, the valve was fulgurated using an endoscopic procedure. During the follow-up period the patient presented normal renal function. Anterior urethral valve is a rare form of urethral anomaly that must be ruled out in boys with pre-natal ultrasound indicating infravesical obstruction. Vesicostomy used as an initial treatment rather than transurethral fulguration may prevent potential complications that can occur due to the small size of the neonatal urethra. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16703 Community Based Medical Journal 2013 July: Vol.02 No 02: 71-74